A service-level action research intervention to improve identification and treatment of cannabis and related mental health issues in young Indigenous Australians: a study protocol. Issue 7 (31st July 2014) - Bohanna, India; Bird, Katrina; Copeland, Jan; Roberts, Nicholas; Clough, Alan
Abstract : Introduction: Regular cannabis use is associated with negative mental health impacts including psychosis, depression and anxiety. Rates of cannabis use have increased in Aboriginal and Torres Strait Islander communities in northern Australia within the last two decades, presenting a significant increased risk to young people's mental health in these regions. Improved screening, early detection and treatment for cannabis-related mental health issues are urgently required. This paper describes a service-level action research intervention and evaluation protocol for use in the few services where it is possible to engage young Aboriginal and Torres Strait Islander Australians. Methods/Design: The protocol is being developed in two services where youth mental health is core business: a primary healthcare centre and a youth service in the Cairns and hinterland region, far north Queensland. The protocol calls first for baseline data to be collected using staff and client surveys; network mapping; and analysis of screening, treatment and referral rates. The protocol's intervention phase is driven by service needs identified from baseline data. Intervention strategies focus on implementing/enhancing cannabis screening instruments and processes in line with current best practice; enhancing networks with external drug and mental health services; developing culturally acceptable training and resources; developing activities aiming to reduce cannabis use in young Aboriginal and Torres Strait Islander clients using the services. The protocol requires implementation of the multilevel intervention within each service for 1 year, with follow-up data then collected and compared to baseline. Process evaluation identifies the more effective intervention strategies and documents the challenges to be overcome for full implementation. Ethics and dissemination: Ethics approval was provided by The James Cook University, Human Research Ethics Committee. Ethics Approval Number H5322. Peer-reviewed publications will also be used to disseminate the finding. Results will also be discussed with stakeholder organisations.